OVERCONFIDENCE CEO PADA PERUSAHAAN EFEK DAN ASURANSI TAHUN 2014-2018 DI BURSA EFEK INDONESIA - Tri Damayanti; Nova Anggrainie; Dini Andriyani (Gapenas Publisher, 2022)
The purpose of this study was to determine the effect of CEO Overconfidence on Securities Companies and Insurance Companies in Indonesia. The population of this research is Securities Companies and Insurance Companies, which are 27 companies consisting of 12 Securities Companies and 15 Insurance Companies. This research was conducted by examining data in the 2014-2018 period with a total sample of 135 samples. The analysis technique used is the Crosstabulation Test, Descriptive Analysis of the Different Tests with Independent-Sample T Test, Descriptive Analysis of the Different Tests with One-Way ANOVA. Crosstabulation Test Results stated that in 2014 the number of companies that overconfidated amounted to 25 companies, in 2015 the number of companies that overconfidzed amounted to 24 companies, in 2016 the number of companies overconfidensed amounted to 22 companies, in 2017 the number of companies that overconfidzed amounted to 19 companies, and in 2018 the number of companies that overconfidated amounted to 27 companies, the results of the Descriptive Analysis Test Different Tests with Independent-Sample T Test states that the condition of the Yield and DER ratio of Insurance Companies is higher than that of Securities Companies this can be seen from the absolute value on average, while for Asset Growth and Sales Growth, Securities Companies are higher. Descriptive Analysis of the Test Results with One-Way ANOVA states that the Yield value varies between years (2014,2015,2016,2017,2018) while the others are not different. This can be seen from the significance value, sig. Yields are below 0.05 while others are above them